Two new species of Anisotaenia (Apiaceae) from Kurdistan, Western Iran - Rastegar, Azad; Maroofi, Hosein; Ghaderi, Hiva (Phytotaxa, 2025)
Two new species, Anisotaenia ghazanfarii and Anisotaenia avromanica from Kurdistan Province of Iran, are described and illustrated as new to science. The main morphological differences between these new species and related taxa are discussed, and the diagnostic characteristics, including the anatomical features of the mericarps, are given in detail. A distribution map and ecological notes on their habitats are provided as well.